The HVEM-BTLA Immune Checkpoint Restrains Murine Chronic Cholestatic Liver Injury by Regulating the Gut Microbiota - Kou, Yanbo; Zheng, Xingping; Meng, Liyuan; Liu, Mengnan; Xu, Shihong; Jing, Qiyue; Zhang, Shenghan; Wang, Hanying; Han, Jinzhi; Liu, Zhuanzhuan; Wei, Yanxia; Wang, Yugang (Frontiers in Immunology, 2022)
The herpes virus entry mediator (HVEM) is an immune checkpoint molecule regulating immune response, but its role in tissue repair remains unclear. Here, we reported that HVEM deficiency aggravated hepatobiliary damage and compromised liver repair after 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC)-induced injury. A similar phenotype was observed in B and T lymphocyte attenuator (BTLA)-deficient mice. These were correlated with impairment of neutrophil accumulation in the liver after injury. The hepatic neutrophil accumulation was regulated by microbial-derived secondary bile acids. HVEM-deficient mice had reduced ability to deconjugate bile acids during DDC-feeding, suggesting a gut microbiota defect. Consistently, both HVEM and BTLA deficiency had dysregulated intestinal IgA responses targeting the gut microbes. These results suggest that the HVEM-BTLA signaling may restrain liver injury by regulating the gut microbiota.